The impact of institutional and socio-ecological drivers on activity at older ages - Izabela Styczyńska; Aart-Jan Riekhoff; Maciej Lis; Agnieszka Kamińska (Center for Social and Economic Research (CASE), 2013)
We present an insight of the socio-economic drivers of economic and noneconomic activity of persons 50+ as well their ability to adopt to SET. Not only the labour market participation, but also social engagement, beliefs, education, religious activities and housework are studied. With the use of European Social Survey data we investigate the general level of the activity among people aged 50+ in Europe as well as the relation between various aspects of activity and general labour market performance. We obtain mixed results on the concomitance of non-market and labour-market activities. We also check the role of personal traits as well as pull and push factors on prematurely leaving labour market in European countries. The differences among countries in terms of the results are confronted with the institutional characteristics of the countries. Finally, selected case studies of successful activation policies are presented.
Keywords: J24; J31; 330; Productivity; Age-Earning Profiles; Lifelong Learning